A method for removing the coating around TBC solar cell silicon wafer using laser
Through the combination of three-step laser treatment and alkali cleaning, the complexity and cost of TBC solar cell silicon wafer winding removal are solved, and efficient and environmentally friendly winding removal is achieved, which improves battery performance and production efficiency.
Patent Information
- Application Number
- CN202411358611.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-27
Smart Images

Figure CN118888646B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of solar cells, and in particular to a method for removing a coating around a TBC solar cell silicon wafer by using laser. Background Art
[0002] In the process of preparing TOPCon and other solar cells, high-temperature diffusion and deposition of poly-Si are important processes for forming pn junctions and high-low junctions in the cells. In order to increase the production output of cells and reduce the cost of single-wafer preparation, tubular vacuum equipment has gradually replaced plate vacuum equipment. However, in the process of tubular diffusion or deposition, whether it is a single-insertion process or a double-insertion process for silicon wafers, it is inevitable that the dielectric film will be affected by the plating, resulting in poor battery aesthetics and large leakage values, which affects battery performance.
[0003] Currently, the industry generally uses wet chemical methods to remove the wrapping layer on the front and side of the silicon wafer, including: (1) using chain acid (HF) to remove the BSG layer / PSG layer + alkali corrosion to remove the wrapping layer; (2) chain acid (HF+HNO3) polishing to remove the wrapping layer. Method (1) is currently only applicable to PERC and TOPCon conventional cells. For TBC cells, due to the presence of p in the wrapping part, + / n + -poly-Si composite laminated structure, such as Figure 1 As shown, the chain acid (HF) removal of BSG layer / PSG layer + alkaline corrosion can only remove the surface phosphorus diffusion layer. The bottom boron diffusion layer cannot be removed in one go and requires a second repeated process, which makes the overall de-plating process very complicated and time-consuming, making it difficult to apply to mass production. Although method (2) can remove the plating layer of PERC, TOPCon, and BC type batteries in one step, due to the thin silicon wafer, the silicon wafer shakes up and down greatly during the acid polishing process, resulting in the inability to effectively remove the edge plating area. In addition, the amount of HF and HNO3 used in the acid polishing process is also large, which undoubtedly increases the difficulty and cost of waste liquid and waste gas treatment.
[0004] In summary, it is necessary to develop a simpler, more efficient, less negative impact, environmentally friendly and low-cost method to remove the silicon wafer coating. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a method for removing the winding coating of TBC solar cell silicon wafers by laser. The present invention adopts the "three-step method" of laser treatment + alkaline cleaning to remove the winding coating on the front and side of the silicon wafer, which has the characteristics of high efficiency, small negative impact, environmental protection and low cost.
[0006] The specific technical solution of the present invention is: a method for removing the coating around the silicon wafer of a TBC solar cell by using laser, which specifically comprises the following steps:
[0007] S1. Select a TBC semi-finished silicon wafer with a coating on the front and side surfaces.
[0008] During the early high-temperature deposition and diffusion process of silicon wafers, it is inevitable that wrap-around layers will be formed on the front and side areas. If these wrap-around layers are not removed, it will not only affect the appearance of the battery, but more importantly, it will increase the leakage value of the battery, thereby affecting the battery performance.
[0009] S2. Laser patterning and grooving are used to initially remove the deposited layer at the junction of the p-region and the n-region on the back side of the silicon wafer, so that an isolation region is initially formed on the back side of the silicon wafer in this area.
[0010] Laser grooving can basically remove the deposited layer at the junction of the p-region and the n-region on the back of the silicon wafer, so that the area can form an insulating isolation area and pave the way for the subsequent alkaline cleaning and texturing to form a pyramid velvet surface.
[0011] S3. The coating on the front side of the silicon wafer is initially removed by three steps of ultraviolet femtosecond laser, green picosecond laser and infrared nanosecond laser.
[0012] In S2, since the deposited layers on the back of the silicon wafer usually only have a boron / phosphorus diffusion layer and a BSG / PSG layer in the same thickness direction, and the thickness is relatively thin, they can be basically removed by a single laser treatment. However, the present invention finds that it is difficult to effectively remove the winding coating on the front and side surfaces of the silicon wafer by only a single laser treatment. The reasons are analyzed as follows: (1) First, the winding coating is usually a stacked winding coating (i.e., a tunneling oxide layer, a boron diffusion layer, a BSG layer, a tunneling oxide layer, a phosphorus diffusion layer, and a PSG layer are sequentially provided in the same thickness direction), and the thickness is relatively thick; (2) Secondly, deposited layers of different properties have different absorption coefficients for lasers, and lasers of different wavelengths have different processing depths. Therefore, it is impossible to effectively remove all deposited layers in the stacked winding coating at the same time by only a single laser treatment.
[0013] To this end, the present invention cleverly adopts a "three-step method" of laser treatment (S3, S5) + alkali cleaning (S6). The "three-step method" of laser treatment specifically includes: first ultraviolet femtosecond laser treatment, then green light picosecond laser treatment, and finally infrared nanosecond laser treatment.
[0014] Different laser wavelengths penetrate the deposited layer to different depths. The penetration depth of the ultraviolet band is 200-400 nm, the penetration depth of the green light band is 492-577 nm, and the penetration depth of the infrared band is >760 nm. The advantages of the "three-step method" laser treatment of the present invention are: (1) through three different laser wavelengths (short wave to medium wave and then to infrared), each deposited layer in the entire stacked coating can be effectively penetrated; (2) under different pulse widths (femtosecond, picosecond, nanosecond), the pulse width of the femtosecond laser is the narrowest, and the energy of a single laser beam is often the highest, which can rapidly heat up the material in a short time, so that the "gasification" effect of the deposited layer dominates during the treatment process; secondly, the pulse width of the picosecond laser is in the middle, and the "gasification" and "fluffing" effects of the deposited layer exist simultaneously during the treatment process; while for the nanosecond laser, the pulse width is the largest, and the energy of a single laser beam is often the lowest, so that the "fluffing" effect of the deposited layer dominates during the treatment process. Therefore, the ultraviolet femtosecond laser treatment can vaporize most of the surface phosphorus diffusion layer / PSG layer, and then the green light picosecond laser treatment can partially "vaporize" and "fluffy" the interface area between the phosphorus diffusion layer / PSG layer and the boron diffusion layer / BSG layer. Finally, the infrared nano-laser treatment makes the boron diffusion layer / BSG layer more "fluffy", paving the way for subsequent effective wet cleaning. Based on different laser pulse widths, the surface deposited layer transitions from the "vaporized" to the "fluffy" state, which can more thoroughly process each deposited layer in the coating.
[0015] S4, stacking multiple silicon wafers obtained in S3 in layers.
[0016] From the perspective of looking down at the front of the silicon wafer, the longitudinal thickness of the side coating is comparable to the thickness of the silicon wafer itself. The side coating area cannot be completely removed during the above-mentioned S3 front laser treatment process; and because the silicon wafer is very thin, it is also impossible to laser process the coating on the four sides of a single silicon wafer. For this reason, the present invention ingeniously stacks the silicon wafers after the front treatment in a "layered" manner, with the side facing up, to prepare for the subsequent laser treatment of the four-side coating.
[0017] S5. The wrap-around coating layers on the four sides of the stacked silicon wafer are processed by ultraviolet femtosecond laser, green picosecond laser and infrared nanosecond laser in sequence, so that the wrap-around coating layers on the sides of the silicon wafer are preliminarily removed.
[0018] S6. Alkaline cleaning and texturing to completely remove the plating layer.
[0019] After the aforementioned laser treatment, the plating layer on the surface of the silicon wafer has been preliminarily removed. In S6, the laser-treated silicon wafer is placed in an alkaline texturing tank for wet cleaning and texturing integrated treatment, so that the plating layer is thoroughly cleaned and a pyramid velvet surface is formed on the front of the silicon wafer. For the S2 slotted area (i.e., isolation area) on the back of the silicon wafer, the residual deposition layer in the isolation area can also be cleaned during the wet cleaning + texturing process, and a pyramid velvet surface is formed. Due to the presence of the PSG layer / BSG layer in the non-S2 slotted area on the back of the silicon wafer, the deposition layer at the bottom of this part can be protected from being damaged during the alkaline cleaning + texturing process.
[0020] Preferably, in S1: the winding coating is a tunneling oxide layer, a boron diffusion layer, a BSG layer, a tunneling oxide layer, a phosphorus diffusion layer and a PSG layer sequentially deposited on the surface of the silicon wafer, with a total thickness of 200-1000 nm.
[0021] Preferably, in S1: the p-region and the n-region on the back side of the silicon wafer are arranged alternately, the deposited layers of the p-region are the tunneling oxide layer, the boron diffusion layer and the BSG layer deposited sequentially on the back side of the silicon wafer, and the deposited layers of the n-region are the tunneling oxide layer, the phosphorus diffusion layer and the PSG layer deposited sequentially on the back side of the silicon wafer, with a total thickness of 100-500 nm.
[0022] Preferably, in S2, the conditions for the laser patterning grooving are: using a picosecond laser, a laser wavelength of 400-600 nm, a spot size of 50-150 μm, a frequency of 500-700 KHz, a marking speed of 40000-50000 mm / s, a power of 10-50 W, and a processing time of 1-5 s.
[0023] Preferably, in S3 and S5:
[0024] The conditions of the ultraviolet femtosecond laser are: laser band 200-400 nm, spot size 20-80 μm, frequency 100-300 KHz, marking speed 10000-30000 mm / s, power 5-100 W, and processing time 1-10 s;
[0025] The conditions of the green picosecond laser are: laser band 492-577 nm, spot size 50-150 μm, frequency 500-700 KHz, marking speed 30000-50000 mm / s, power 5-100 W, and processing time 1-10 s;
[0026] The conditions of the infrared nanosecond laser are: laser band 760~1200 nm, spot size 100~300 μm, frequency 800~1200 KHz, marking speed 50000~80000 mm / s, power 5~100 W, and processing time 1~10 s.
[0027] The present invention finds that in order to further improve the removal effect of the coating, the wavelength and frequency of the three laser treatments can be set differently. Specifically, a small spot size / low frequency ultraviolet femtosecond laser treatment is performed first, followed by a medium spot size / medium frequency green light picosecond laser treatment, and finally a large spot size / high frequency infrared nanosecond laser treatment.
[0028] First of all, for different laser spot sizes, the size of the spot directly affects the energy distribution within the spot. When the laser power is constant, if the spot size increases, the single energy density will decrease because the energy is dispersed over a larger area; the smaller the spot size, the higher the energy density. The spot size determines the degree of focusing of the laser beam. The shorter the focal length, the tighter the laser beam is focused, the smaller the spot formed, but the higher the energy density within the spot. Conversely, the longer the focal length, the larger the spot, and the lower the energy density. Therefore, for ultraviolet femtosecond lasers, small spots are more likely to obtain higher single energy densities, making the "gasification" effect of the deposited layer more significant; for green picosecond lasers, the spot size is moderate, the single energy density is also moderate, and the "gasification" and "fluffy" effects are taken into account at the same time when processing the deposited layer; and for infrared nanosecond lasers, the spot size is the largest and the single energy density is the lowest, and the "fluffy" effect will be more significant when processing the deposited layer.
[0029] Secondly, different laser frequencies will significantly affect the energy of a single laser beam. When the laser output power is constant, the lower the frequency, the greater the energy of a single laser beam, and vice versa. This is because the energy of a single laser is related to the repetition frequency of the laser, and the output power is the product of the single laser energy and the repetition frequency. Specifically: the repetition frequency refers to the number of pulses emitted by the laser per unit time. When the output power is constant, the high or low repetition frequency will affect the energy of a single pulse. Increasing the repetition frequency will cause the energy of a single pulse to decrease, because the output power is fixed, and more pulses mean that the energy carried by each pulse is reduced; if the frequency increases, the energy of a single pulse will decrease accordingly to keep the output power unchanged. This is because the output power is the product of the energy of a single pulse and the repetition frequency, and increasing the frequency will inevitably lead to a decrease in the energy of a single pulse.
[0030] Therefore, low-frequency lasers often have the largest single energy, and can process deposited layers to make them have a greater "gasification" effect. High-frequency lasers often have the smallest single energy, and can process deposited layers to make them have a greater "fluffy" effect. The frequency can be adjusted to further make the "gasification" and "fluffy" effects in the above laser processing process more significant.
[0031] Preferably, in S4: after the layered stacking, the front side of the lower silicon wafer is in contact with the back side of the upper silicon wafer, and after the layered stacking, the four side surfaces of all the silicon wafers are flush.
[0032] Preferably, in S5: the coating layers on four sides of all silicon wafers after layered stacking are processed in sequence by laser.
[0033] After laser processing one side, the stacked silicon wafer can be rotated 90° clockwise and then the next side of the coating layer can be processed. A total of 4 sides are processed in sequence. The schematic diagram of the entire processing flow is shown in the figure. Figure 2 shown.
[0034] Preferably, in S6, the alkaline cleaning and texturing specifically includes: placing the silicon wafer into an alkaline texturing tank for wet cleaning and integrated texturing treatment to completely remove the residual plating layer on the surface of the silicon wafer and the residual deposition layer in the S2 grooved area; at the same time, a pyramid velvet surface is formed on the surface of the grooved area on the front and back sides of the silicon wafer.
[0035] Preferably, in S6, the alkaline cleaning and texturing is finally performed by acid washing to remove the PSG layer and the BSG layer remaining in the non-grooving area S2 on the back side of the silicon wafer.
[0036] Compared with the prior art, the beneficial effects of the present invention are:
[0037] (1) The present invention ingeniously adopts the "three-step method" of laser processing + alkaline cleaning to remove the plating layer on the front and side of the silicon wafer, which has the characteristics of high efficiency, small negative impact, environmental protection and low cost.
[0038] (2) The present invention stacks the silicon wafers after front-side de-coating in a "layered" manner and then performs laser processing together, which not only solves the problem that a single silicon wafer cannot be laser processed individually due to its thin thickness, but also improves batch processing efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 Schematic diagram of the structure of the TBC semi-finished silicon wafer with the winding coating in S1 of the present invention.
[0040] Figure 2 It is a schematic diagram of the process of laser processing the front and side coating of a silicon wafer according to the present invention.
[0041] Figure 3 This is a schematic diagram of the structure of the silicon wafer after alkaline cleaning and texturing according to the present invention.
[0042] The reference numerals in the drawings are: silicon wafer 1 , tunnel oxide layer 2 , boron diffusion layer 3 , BSG layer 4 , phosphorus diffusion layer 5 , PSG layer 6 , and pyramid velvet surface 7 . DETAILED DESCRIPTION
[0043] The present invention will be further described below in conjunction with the embodiments.
[0044] Overall embodiment
[0045] A method for removing a coating around a TBC solar cell silicon wafer by using a laser comprises the following steps:
[0046] S1. Select TBC semi-finished silicon wafers with wrap-around coating on the front and sides. During the early high-temperature diffusion and deposition process of the silicon wafer, wrap-around coating will inevitably appear on the front and side areas. If these wrap-around coatings are not removed, it will not only affect the appearance of the battery, but more importantly, it will increase the leakage value of the battery, thereby affecting the battery performance.
[0047] In some specific implementation cases, the thickness of the silicon wafer is ≤150 μm.
[0048] In some specific implementation cases, such as Figure 1 As shown, the coating layer is a tunneling oxide layer 2, a boron diffusion layer 3, a BSG layer 4, a tunneling oxide layer 2, a phosphorus diffusion layer 5 and a PSG layer 6 deposited sequentially on the surface of the silicon wafer 1, with a total thickness of 200-1000 nm.
[0049] In some specific implementation cases, such as Figure 1 As shown, the p-region and the n-region on the back side of the silicon wafer 1 are alternately arranged, the deposited layers of the p-region are the tunneling oxide layer 2, the boron diffusion layer 3 and the BSG layer 4 deposited sequentially on the back side of the silicon wafer, and the deposited layers of the n-region are the tunneling oxide layer 2, the phosphorus diffusion layer 5 and the PSG layer 6 deposited sequentially on the back side of the silicon wafer, with a total thickness of 100-500 nm.
[0050] S2. Laser patterning and grooving are used to initially remove the deposited layer at the junction of the p-region and the n-region on the back of the silicon wafer, so that an isolation zone is initially formed on the back of the silicon wafer in this area. Laser grooving can basically remove the deposited layer at the junction of the p-region and the n-region on the back of the silicon wafer. After grooving, an insulating isolation zone can be initially formed in this area, and a foundation is laid for the subsequent alkaline cleaning and velveting to form a pyramid velvet surface.
[0051] In some specific implementation cases, the conditions for the laser patterning grooving are: using a picosecond laser, a laser wavelength of 400~600 nm, a spot size of 50~150 μm, a frequency of 500~700 KHz, a marking speed of 40000~50000 mm / s, a power of 10~50 W, and a processing time of 1~5 s.
[0052] S3. The coating on the front side of the silicon wafer is initially removed by three steps of ultraviolet femtosecond laser, green picosecond laser and infrared nanosecond laser.
[0053] In some specific implementation cases, the conditions of the ultraviolet femtosecond laser are: spot size of 20~80 μm, laser band of 200~400 nm, frequency of 100~300 KHz, marking speed of 10000~30000 mm / s, power of 5~100 W, and processing time of 1~10 s.
[0054] In some specific implementation cases, the conditions of the green picosecond laser are: spot size of 50~150 μm, laser band of 492~577 nm, frequency of 500~700 KHz, marking speed of 30000~50000 mm / s, power of 5~100 W, and processing time of 1~10 s.
[0055] In some specific implementation cases, the conditions of the infrared nanosecond laser are: spot size of 100~300 μm, laser band of 760~1200 nm, frequency of 800~1200 KHz, marking speed of 50000~80000 mm / s, power of 5~100 W, and processing time of 1~10 s.
[0056] S4, stacking multiple silicon wafers obtained from S3 in layers. From the perspective of looking down at the front of the silicon wafer, the longitudinal thickness of the side coating is equivalent to the thickness of the silicon wafer itself. The side coating cannot be completely removed during the above-mentioned S3 front laser treatment process; and because the silicon wafer is very thin, it is also impossible to process the coating on the four sides of a single silicon wafer by laser. For this reason, the present invention cleverly stacks the silicon wafers after the above-mentioned front treatment in "layers", with the side facing up, to prepare for the subsequent laser treatment of the four-side coating.
[0057] In some specific implementation cases, after the layered stacking, the front side of the lower silicon wafer is attached to the back side of the upper silicon wafer, and after the layered stacking, the four side surfaces of all silicon wafers are flush.
[0058] S5. The wrap-around coating layers on the four sides of the stacked silicon wafer are processed by ultraviolet femtosecond laser, green picosecond laser and infrared nanosecond laser in sequence, so that the wrap-around coating layers on the sides of the silicon wafer are initially removed.
[0059] In some specific implementation cases, the coating layers on the four sides of all silicon wafers after the stacking are processed sequentially by laser. After the laser processing of one side, the stacked silicon wafer can be rotated 90° clockwise and then the coating layers on the next side are processed. A total of four sides are processed sequentially. The schematic diagram of the entire processing flow is shown in FIG. Figure 2 shown.
[0060] In some specific implementation cases, the conditions of the ultraviolet femtosecond laser are: spot size of 20~80 μm, laser band of 200~400 nm, frequency of 100~300 KHz, marking speed of 10000~30000 mm / s, power of 5~100 W, and processing time of 1~10 s.
[0061] In some specific implementation cases, the conditions of the green picosecond laser are: spot size of 50~150 μm, laser band of 492~577 nm, frequency of 500~700 KHz, marking speed of 30000~50000 mm / s, power of 5~100 W, and processing time of 1~10 s.
[0062] In some specific implementation cases, the conditions of the infrared nanosecond laser are: spot size of 100~300 μm, laser band of 760~1200 nm, frequency of 800~1200 KHz, marking speed of 50000~80000 mm / s, power of 5~100 W, and processing time of 1~10 s.
[0063] S6, alkaline cleaning and texturing, completely remove the winding plating layer. After the above laser treatment, the winding plating layer on the surface of the silicon wafer has been preliminarily removed. Figure 3 As shown, in S6, the silicon wafer after laser treatment is placed in an alkaline texturing tank for wet cleaning and texturing integrated treatment, so that the coating layer is thoroughly cleaned, and a pyramid texturing surface 7 is formed on the front of the silicon wafer; and for the S2 slotted area (i.e., isolation area) on the back of the silicon wafer, the residual deposition layer in the isolation area can also be cleaned during the wet cleaning + texturing process, and a pyramid texturing surface 7 is formed. As for the non-S2 slotted area on the back of the silicon wafer, the deposition layer at the bottom of this part can be protected from being damaged during the alkaline cleaning + texturing process.
[0064] In some specific implementation cases, the conditions for alkaline cleaning and texturing are: the temperature is maintained at 75-85° C. and the time is 6-12 min.
[0065] S7, double-sided coating: ALD deposition method is used to deposit AlO on the front and back sides of the processed silicon wafer x The film is generated by the reaction of Al(CH3)3 and water vapor, with a thickness of 8~10 nm and a process temperature of 220~280℃. Then SiN is deposited on both sides using a tubular PECVD device. x Film, front SiN x The thickness of the film is 80~100 nm, and the refractive index is 2.0~2.1; the back SiN x The thickness of the film is 80~120 nm, and the refractive index is 1.9~2.1; the reaction gases in the tubular cavity are SiH4 and NH3, the working pressure is 1500~1700 mTorr, the power is 10000~15000 W, the temperature is 400~600℃, the SiH4 gas flow rate is 900~2000 sccm, the NH3 gas flow rate is 7000~12000 sccm, the silicon-nitrogen ratio is 0.1~0.3:1, and the deposition time is 5~20 min.
[0066] S8. The coated silicon wafer is screen-printed on the back to form a metal contact, and then sintered at 700-800°C to form an Ag-Si ohmic contact. Finally, the final TBC solar cell is obtained through light injection repair.
[0067] Specific examples and comparative examples.
[0068] Example 1
[0069] A method for removing a coating around a TBC solar cell silicon wafer by using a laser comprises the following steps:
[0070] S1. Select a TBC semi-finished silicon wafer with a coating on the front and side. The thickness of the silicon wafer is 150 μm and the size is 182.2 mm×183.75 mm. Figure 1 As shown, the winding coating is a tunneling oxide layer 2, a boron diffusion layer 3, a BSG layer 4, a tunneling oxide layer 2, a phosphorus diffusion layer 5 and a PSG layer 6 sequentially deposited on the surface of the silicon wafer 1, with a total thickness of about 600 nm. The p-region and the n-region on the back of the silicon wafer 1 are arranged alternately, and the deposited layers in the p-region are the tunneling oxide layer 2, the boron diffusion layer 3 and the BSG layer 4 sequentially deposited on the back of the silicon wafer, and the deposited layers in the n-region are the tunneling oxide layer 2, the phosphorus diffusion layer 5 and the PSG layer 6 sequentially deposited on the back of the silicon wafer, with a total thickness of about 300 nm.
[0071] S2. Laser patterning and grooving are used to initially remove the deposited layer at the junction of the p-region and the n-region on the back of the silicon wafer, so that an isolation zone is initially formed on the back of the silicon wafer in this area. Laser grooving can basically remove the deposited layer at the junction of the p-region and the n-region on the back of the silicon wafer. After grooving, this area can initially form an insulating isolation zone and pave the way for the subsequent velvet formation to form a pyramid velvet surface. Specifically, the conditions for the laser patterning and grooving are: using a picosecond laser, a laser wavelength of 532 nm, a spot size of 100 μm, a frequency of 600KHz, a marking speed of 45000 mm / s, a power of 50 W, and a processing time of 3 s.
[0072] S3. Preliminary removal of the front side coating of the silicon wafer by three-step treatment using ultraviolet femtosecond laser, green picosecond laser and infrared nanosecond laser. Specifically, the conditions of the ultraviolet femtosecond laser are: spot size of 60 μm, laser band of 355 nm, frequency of 200 KHz, marking speed of 15000 mm / s, power of 60 W, and processing time of 9 s. The conditions of the green picosecond laser are: spot size of 120 μm, laser band of 532 nm, frequency of 600 KHz, marking speed of 35000 mm / s, power of 60 W, and processing time of 6 s. The conditions of the infrared nanosecond laser are: spot size of 250 μm, laser band of 1064 nm, frequency of 1100 KHz, marking speed of 60000 mm / s, power of 60 W, and processing time of 3 s.
[0073] S4, stacking the plurality of silicon wafers obtained in S3 in layers. After the stacking, the front side of the lower silicon wafer is attached to the back side of the upper silicon wafer, and the four sides of all silicon wafers are flush.
[0074] S5. Use ultraviolet femtosecond laser, green picosecond laser and infrared nanosecond laser to process the coating on the four sides of the stacked silicon wafers in sequence, so that the coating on the sides of the silicon wafers is initially removed. Specifically: Use laser to process the coating on the four sides of all the stacked silicon wafers in sequence. After laser processing one side, the stacked silicon wafer can be rotated 90° clockwise and then the coating on the next side can be processed. A total of 4 sides are processed in sequence. The schematic diagram of the entire processing flow is shown as follows: Figure 2 As shown. The conditions of the ultraviolet femtosecond laser are: spot size of 60 μm, laser band of 355 nm, frequency of 200 KHz, marking speed of 15000 mm / s, power of 60 W, and processing time of 9 s. The conditions of the green picosecond laser are: spot size of 120 μm, laser band of 532 nm, frequency of 600 KHz, marking speed of 35000 mm / s, power of 60 W, and processing time of 6 s. The conditions of the infrared nanosecond laser are: spot size of 250 μm, laser band of 1064 nm, frequency of 1100 KHz, marking speed of 60000 mm / s, power of 60 W, and processing time of 3 s.
[0075] S6. After the aforementioned laser treatment, the coating on the surface of the silicon wafer has been preliminarily removed. Figure 3As shown, in S6, the silicon wafer after laser treatment is placed in an alkaline texturing tank for wet cleaning and texturing integrated treatment (the conditions for alkaline cleaning and texturing are: the temperature is maintained at 82°C for 7 minutes, so that the coating layer is thoroughly cleaned and a pyramid velvet surface 7 is formed on the front side of the silicon wafer; and for the S2 slotted area (i.e., the isolation area) on the back side of the silicon wafer, the residual deposition layer in the isolation area can also be cleaned during the wet cleaning + texturing process, and a pyramid velvet surface 7 is formed. As for the non-S2 slotted area on the back side of the silicon wafer, due to the presence of the PSG layer / BSG layer, the deposition layer at the bottom of this part can be protected from being damaged during the alkaline cleaning + texturing process.
[0076] S7, double-sided coating: Atomic layer deposition (ALD) is used to deposit AlO on the front and back of the processed silicon wafer. x The film is generated by the reaction of Al(CH3)3 and water vapor, with a thickness of 8 nm and a process temperature of 250°C. Then, SiN is deposited on both sides of the silicon wafer using a tubular PECVD device. x Thin film, SiN x The film thickness is about 90 nm and the refractive index is 2.0. x During thin film deposition, the reaction gases in the tubular chamber are SiH4 and NH3, the working pressure is 1600 mTorr, the power is 12000 W, the temperature is 440℃, the flow rate of SiH4 gas is 980 sccm, the flow rate of NH3 gas is 8000 sccm, the silicon-nitrogen ratio is 1:5, and the deposition time is 10 min.
[0077] S8. The coated silicon wafer is screen-printed on the back to form a metal contact, and then sintered at 770°C to form an Ag-Si ohmic contact. Finally, the final TBC solar cell is obtained through light injection repair.
[0078] Example 2
[0079] The difference between Example 2 and Example 1 is that S3 and S5 adopt the "three-step method" laser treatment, but use the same frequency. The specific laser treatment process is:
[0080] The coating on the front and side of the silicon wafer was initially removed by three-step treatment using ultraviolet femtosecond laser, green picosecond laser and infrared nanosecond laser. Specifically, the conditions of the ultraviolet femtosecond laser are: spot size of 60 μm, laser band of 355 nm, frequency of 600 KHz, marking speed of 15000 mm / s, power of 60 W, and processing time of 9 s. The conditions of the green picosecond laser are: spot size of 120 μm, laser band of 532 nm, frequency of 600 KHz, marking speed of 35000 mm / s, power of 60 W, and processing time of 6 s. The conditions of the infrared nanosecond laser are: spot size of 250 μm, laser band of 1064 nm, frequency of 600 KHz, marking speed of 60000 mm / s, power of 60 W, and processing time of 3 s.
[0081] Example 3
[0082] The difference between Example 3 and Example 1 is that S3 and S5 adopt the "three-step method" laser processing, but use the same spot size. The specific laser processing process is:
[0083] The coating on the front and side of the silicon wafer was initially removed by three-step treatment using ultraviolet femtosecond laser, green picosecond laser and infrared nanosecond laser. The conditions of the ultraviolet femtosecond laser are: spot size of 150 μm, laser band of 355 nm, frequency of 200 KHz, marking speed of 15000 mm / s, power of 60 W, and processing time of 9 s. The conditions of the green picosecond laser are: spot size of 150 μm, laser band of 532 nm, frequency of 600 KHz, marking speed of 35000 mm / s, power of 60 W, and processing time of 6 s. The conditions of the infrared nanosecond laser are: spot size of 150 μm, laser band of 1064 nm, frequency of 1100 KHz, marking speed of 60000 mm / s, power of 60 W, and processing time of 3 s.
[0084] Comparative Example 1
[0085] The difference between Comparative Example 1 and Example 1 is that a conventional pickling process is used to remove the plating layer on the front and side surfaces of the silicon wafer, which specifically includes the following steps:
[0086] The difference between Comparative Example 1 and Example 1 is that S3-S5 of Example 1 are replaced by: the silicon wafer after high-temperature treatment is passed through a chain acid polishing etcher to remove the coating on the front and side surfaces of the silicon wafer, wherein the volume ratio of the hydrofluoric acid solution and the nitric acid solution in the acid tank is 1:4 (the concentration of the hydrofluoric acid solution is 49 wt%, and the concentration of the nitric acid solution is 69 wt%), and the belt speed is 1.3 m / min.
[0087] Comparative Example 2
[0088] The difference between Comparative Example 2 and Example 1 is that S3 and S5 are treated with laser once. The specific laser treatment process is: picosecond laser, laser wavelength 532 nm, spot size 100 μm, frequency 600 KHz, marking speed 45000 mm / s, power 50 W, and treatment time 3 s.
[0089] Performance
[0090] The TBC solar cells obtained in the embodiments and comparative examples were subjected to various performance tests, and the results are shown in Table 1:
[0091] Table 1
[0092]
[0093] From the comparison of the data in Table 1, we can see that:
[0094] Example 1 uses a differentiated "three-step" laser process to remove the coating, and combined with alkaline cleaning, it can effectively remove the coating on the front and side of the silicon wafer. The results show that the TBC solar cell has the highest conversion efficiency and the lowest leakage value.
[0095] For Example 2 and Example 3, although the differentiated "three-step" laser process is also used to remove the coating, the parameter differentiation of the three-step laser processing process is not significant compared with Example 1 (the laser power remains unchanged in Example 2, and the spot size remains unchanged in Example 3), so the corresponding leakage current value is slightly higher.
[0096] As for Comparative Example 1, since the conventional chain acid polishing method is used to remove the plating layer on the front and sides of the silicon wafer, the silicon wafer is relatively thin, and the silicon wafer often shakes up and down greatly during the acid polishing process, resulting in the inability to effectively remove the edge plating area, which will lead to a higher leakage value and affect the final battery performance.
[0097] As for Comparative Example 2, since the conventional "one-step" laser process is used, the coating on the front and sides cannot be effectively removed, so the battery leakage value is the highest, which significantly affects the battery performance.
[0098] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0099] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for removing the coating around the silicon wafer of a TBC solar cell by using laser, characterized in that include: S1, select a TBC semi-finished silicon wafer with a coating on the front and side surfaces; S2, laser patterning and grooving to initially remove the deposited layer at the junction of the p-region and the n-region on the back of the silicon wafer, so that an isolation region is initially formed on the back of the silicon wafer in the grooving area; S3, removing the coating on the front side of the silicon wafer by three steps of ultraviolet femtosecond laser, green picosecond laser and infrared nanosecond laser; S4, stacking multiple silicon wafers obtained in S3 in layers; S5, treating the wrap-around coating layers on four sides of the stacked silicon wafers by ultraviolet femtosecond laser, green picosecond laser and infrared nanosecond laser, so that the wrap-around coating layers on the sides of the silicon wafers are preliminarily removed; S6. Alkaline cleaning and texturing to completely remove the plating layer.
2. The method according to claim 1, characterized in that: In S1: the winding coating layer is a tunneling oxide layer, a boron diffusion layer, a BSG layer, a tunneling oxide layer, a phosphorus diffusion layer and a PSG layer deposited on the surface of the silicon wafer in sequence.
3. The method according to claim 2, characterized in that: In S1: the p-region and n-region on the back of the silicon wafer are arranged alternately, the deposited layers of the p-region are the tunneling oxide layer, the boron diffusion layer and the BSG layer deposited in sequence on the back of the silicon wafer, and the deposited layers of the n-region are the tunneling oxide layer, the phosphorus diffusion layer and the PSG layer deposited in sequence on the back of the silicon wafer.
4. The method according to claim 3, characterized in that: In S1: The total thickness of the winding coating is 200-1000 nm; The total thickness of the deposited layers of the p-region and the n-region is 100-500 nm.
5. The method according to claim 1, characterized in that: In S2, the conditions for the laser patterning grooving are: using a picosecond laser, a laser wavelength of 400-600 nm, a spot size of 50-150 μm, a frequency of 500-700 KHz, a marking speed of 40000-50000 mm / s, a power of 10-50 W, and a processing time of 1-5 s.
6. The method according to claim 1 or 2, characterized in that: In S3 and S5: The conditions of the ultraviolet femtosecond laser are: spot size 20-80 μm, laser band 200-400 nm, frequency 100-300 KHz, marking speed 10000-30000 mm / s, power 5-100 W, and processing time 1-10 s; The conditions of the green picosecond laser are: spot size 50-150 μm, laser band 492-577 nm, frequency 500-700 KHz, marking speed 30000-50000 mm / s, power 5-100 W, and processing time 1-10 s; The conditions of the infrared nanosecond laser are: spot size 100~300 μm, laser band 760~1200 nm, frequency 800~1200 KHz, marking speed 50000~80000 mm / s, power 5~100 W, and processing time 1~10 s.
7. The method according to claim 1, characterized in that: In S4: after the layered stacking, the front side of the lower silicon wafer is in contact with the back side of the upper silicon wafer, and after the layered stacking, the four side surfaces of all silicon wafers are flush.
8. The method according to claim 1 or 7, characterized in that: In S5: the coating layers on four sides of all silicon wafers after layer stacking are processed in sequence by laser.
9. The method according to claim 1, characterized in that: In S6, the alkaline cleaning and texturing specifically includes: placing the silicon wafer into an alkaline texturing tank for wet cleaning and integrated texturing treatment to completely remove the residual plating layer on the surface of the silicon wafer and the residual deposition layer in the S2 slotting area; at the same time, a pyramid velvet surface is formed on the surface of the slotting area on the front and back sides of the silicon wafer.
10. The method according to claim 9, characterized in that: In S6, the alkaline cleaning and texturing is finally carried out by acid washing to remove the PSG layer and the BSG layer remaining in the non-grooving area S2 on the back side of the silicon wafer.
